Molecular profile of ultrastructure changes of the ligamentum flavum related to lumbar spinal canal stenosis. Issue 7 (1st March 2019) - Sidon, Eliezer; Shemesh, Shai S.; Mor‐Yossef Moldovan, Lisa; Wiesenfeld, Yarden; Ohana, Nissim; Benayahu, Dafna
Abstract: Lumbar spinal canal stenosis (LSCS) is a degenerative disease observed by hypertrophy of the ligamentum flavum (LF) that cause compression of the lumbar neural content. Diabetes mellitus (DM) is a risk factor for the disease and we have shown previously that DM increases the fibrosis and elastic fiber loss in patients with LSCS. The purpose of this study was to find the proteins that play a role in the development of this clinical pathogenesis and the effect of DM on protein expression. LF tissue retrieved from patients diagnosed with LSCS, some were also diagnosed with DM, were compared with LF from patients diagnosed with herniated nucleus pulposus (HNP). The tissues were analyzed by mass spectrometry for proteins profile alteration. We found that LF of LSCS/DM patients exhibited significantly higher levels of proteoglycan proteins and latent transforming growth factor β‐binding protein (LTBP2 and LTBP4). Additionally, an increase of HTRA serine protease 1 and insulin‐like growth factor binding protein‐5 were noted. The higher fibrosis was also associated with proteins related to inflammation and slower tissue repair. Collagen 6 and transforming growth factor inhibitor are related to activation of the anti‐inflammatory M2 pathway that is associated with tissue repair. The decrease of these proteins expression in LSCS/DM is associated with increased levels and activation of M1 pro‐inflammatory pathways. Interestingly, C3 and C4b members of the complement complex and mannose receptor‐like protein (CLEC18) paralogous proteins were detectable solely at the LSCS/DM patients' samples. Histology analysis shows that inflammatory was induced by the hyperglycemic conditions in diabetic patients involve in altering the matrix compositions. Thus, the protein profiles associated with inflammatory pathways affecting the LF suggested increasing susceptibility of developing the degeneration under hyperglycemic conditions. Abstract : We present our work studying the molecular basis of ligamentum flavus hypertrophy, with and without the influence of diabetes mellitus. We found difference in protein expression that is associated with fibrosis, chondral metaplasia, and hyperglycemia.